High Glycemic Diet Is Related to Brain Amyloid Accumulation Over One Year in Preclinical Alzheimer's Disease - Taylor, Matthew K.; Sullivan, Debra K.; Morris, Jill K.; Vidoni, Eric D.; Honea, Robyn A.; Mahnken, Jonathan D.; Burns, Jeffrey M. (Frontiers in Nutrition, 2021)
OBJECTIVE: To test the hypothesis that high glycemic diet is related to 1-year change in brain amyloid based on our prior cross-sectional evidence that high glycemic diet is associated with brain amyloid. METHODS: This longitudinal, observational study assessed the relationship between reported habitual consumption of a high glycemic diet (HGDiet) pattern and 1-year brain amyloid change measured by Florbetapir F18 PET scans in 102 cognitively normal older adults with elevated or sub-threshold amyloid status that participated in a 1-year randomized, controlled exercise trial at the University of Kansas Medical Center in Kansas City. RESULTS: Among all participants (n=102), higher daily intake of the HGDiet pattern (β=0.06, p=0.04), sugar (β=0.07, p=0.01), and total carbohydrate (β=0.06, p=0.04) were related to more precuneal amyloid accumulation. These relationships in the precuneus were accentuated in participants with elevated amyloid at enrollment (n=70) where higher intake of the HGDiet pattern, sugar, and carbohydrate were related to more precuneal amyloid accumulation (β=0.11, p=0.01 for all measures). In individuals with elevated amyloid, higher intake of the HGDiet pattern was also related to more amyloid accumulation in the lateral temporal lobe (β=0.09, p<0.05) and posterior cingulate gyrus (β=0.09, p<0.05) and higher sugar and carbohydrate intake were also related to more amyloid accumulation in the posterior cingulate gyrus (β=0.10, p<0.05 for both measures). CONCLUSION: This longitudinal observational analysis suggests that a high glycemic diet relates to higher brain amyloid accumulation over one year in regions of the temporoparietal cortex in cognitively normal adults, particularly in those with elevated amyloid status. Further studies are required to assess whether there is causal link between a high glycemic diet and brain amyloid.